Avaliação de biomarcadores em pacientes pediátricos neutropênicos com leishmaniose visceral e onco-hematológicos - Costa, Flávia Oliveira da (2013)
Infection is the major complication for neutropenic patients, and cause of morbidity and mortality. Clinical signs are nonspecific and fever may be a late marker for the early use of antibiotics, which may complicate the prognosis. The approaches of most protocols focus on adult patients. Thus, to improve safety in the clinical approach in pediatric neutropenic patients, this work was performed in order to evaluate biomarkers involved in the inflammatory response in pediatric patients. In the period 2010 to 2012 were included 70 children with neutropenia with neutrophil count ≤ 1000 cells / mm ³, 35 pediatric patients with visceral leishmaniasis (VL) and 35 patients with onco-hematological disease, ranging in age from 0 to 18, from the oncology service of the Hospital Emergency ward Segipe and Pediatrics Diseases, University Hospital of Sergipe. Serum levels of biomarkers were evaluated following: Interferon gamma (IFN-γ), interleukin-5 (IL-5), interleukin-6 (IL-6), interleukin-10 (IL-10), lactate, ultrasensitive CRP (hsCRP), nprocalcitonina (PCT) and Tumor Necrosis Factor-α (TNF-α). The results showed that the average of the groups was no significant difference with biomarkers IFN-γ, IL-10 and TNF-α with p <0.001, IL-5 and p = 0.020, p = 0.002 with lactate and p = 0.011 PCT The hsCRP and IL-6 did not show statistical significance. Correlating CAN groups with the average of biomarkers, there was no statistical significance. This study suggests that biomarkers biomarkers that IFN-γ, IL-5, IL-10, lactate, procalcitonin and TNF-α, laboratory values showed a significant difference between the group of patients neutropenic patients with LV disease and onco- hematologic, this is not happening with the results presented by biomarkers IL-6 and hsCRP, leading us to observe that although the groups have in common neutropenia, interpretation of these biomarkers should be performed separately for each group. Except for lactate and procalcitonin, all other biomarkers showed increased results when comparing the mean of the two groups, which leads us to conclude that studies with larger numbers of subjects are important to verify the use of IFN-γ biomarkers, IL- 5, IL-6, IL-10 and TNF-α in the diagnosis of infection in neutropenic patients.